THE EFFECTS OF LEARNING MANAGEMENT THROUGH MASSIVE OPEN ONLINE COURSES (MOOCs) ON ACADEMIC ACHIEVEMENT IN MATERNAL, NEWBORN, AND MIDWIFERY NURSING AMONG NURSING STUDENTS - Chainakin, Pattiya; Sukjaem, Janyalak; Sriphongsut, Piyathida; Ruenprot, Waranan; Karuna, Sirawan; Vachiravanichakij, Poramapon; Thepbuddee, Sudarat; Phengsuk, Ariya (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This study was a quasi-experimental research using a two-group pretest-posttest design. The objectives were: 1) to compare students’ average score before and after studying through a Massive Open Online Course (MOOCs), and 2) to compare post-intervention average score between students learning through MOOCs and those receiving traditional classroom instruction. The sample consisted of 50 second-year nursing students, selected through purposive sampling based on specific inclusion criteria. They were divided into an experimental group and a control group, with 25 students in each group. The experimental group received learning management through MOOCs, while the control group participated in traditional classroom learning. The research instruments included: 1) a learning management program using MOOCs, and 2) a knowledge test with an index of item-objective congruence (IOC) of .75 - 1.00. The reliability coefficient for the entire test, analyzed using KR-20, was .80. Data were analyzed using paired samples t-test and independent samples t-test. The results showed that both the experimental group and the control group had moderate post-test scores (M = 14.60, SD = 3.44 and M = 9.44, SD = 2.29, respectively). The experimental group showed a statistically significant increase in mean score from pre-test to post-test at the .05 level (t = -10.853, p = .000), and the control group also showed a statistically significant improvement at the .05 level (t = -6.225, p = .000). Moreover, the post-test mean score of the experimental group was significantly higher than that of the control group at the .05 level (t = 6.241, p = .000). In conclusion, learning through MOOCs in maternal, newborn and midwifery nursing led to higher academic achievement in post-intervention than traditional classroom learning. Therefore, the use of MOOCs should be promoted and expanded to other subjects to improve the academic performance of nursing students.